DFMD: Fast and Effective DelPhiForce Steered Molecular Dynamics Approach to Model Ligand Approach Toward a Receptor: Application to Spermine Synthase Enzyme - Peng, Yunhui; Yang, Ye; Li, Lin; Jia, Zhe; Cao, Weiguo; Alexov, Emil (Frontiers in Molecular Biosciences, 2019)
Here we report a novel approach, the DelPhiForce Molecular Dynamics (DFMD) method, for steered molecular dynamics simulations to model receptor-ligand association. The main purpose of developing DFMD is to simulate ligand’s trajectory toward the receptor and thus to predict the “entrance” of the binding pocket and conformational changes associated with the binding. We demonstrate that the DFMD is superior compared with molecular dynamics simulations applying standard cut-offs, provides correct binding forces, allows for modeling the ligand approach at long distances and thus guides the ligand toward the correct binding spot, and it is very fast. The DFMD is applied to model the binding of two ligands to a receptor (spermine synthase) and it is demonstrated that it guides the ligands toward the corresponding pockets despite of the initial ligand’s position with respect to the receptor. Predicted conformational changes and the order of ligand binding are experimentally verified.